CLINICAL FEATURES OF CORONARY ARTERY DISEASE IN PATIENTS RESISTANT TO ANTIPLATELET THERAPY (International Conference on Education and Innovation, 2025)
Cardiovascular diseases are the leading cause of morbidity and mortality among patients with diabetes mellitus. In most diabetic patients, the risk of developing coronary artery disease (CAD) is comparable to that of patients with an established diagnosis of CAD. Improved glycemic control in diabetic patients does not lead to a reduced incidence of CAD. Diabetes is an independent major risk factor for CAD. Several studies have shown that aspirin resistance is associated with fasting blood glucose levels in patients with diabetes.